1997
DOI: 10.1097/00000658-199710000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Is Hypothermia in the Victim of Major Trauma Protective or Harmful?

Abstract: Hypothermia increases fluid requirements and independently increases acute mortality after major trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
1
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(139 citation statements)
references
References 25 publications
1
121
1
12
Order By: Relevance
“…This complication as so many other things is better to prevent than to have to treat later. Prevention is accomplished by hypothermia prevention and treatment [93][94][95][96][97] (Box 1) and shock limitation, which in turn, is guaranteed by rapid interruption of the hemorrhage and aggressive hemodynamic resuscitation. Prophylactic administration of platelets or plasma usually do not prevent coagulopathy [98,99].…”
Section: Transfusion Threshold and Coagulopathy Correctionmentioning
confidence: 99%
“…This complication as so many other things is better to prevent than to have to treat later. Prevention is accomplished by hypothermia prevention and treatment [93][94][95][96][97] (Box 1) and shock limitation, which in turn, is guaranteed by rapid interruption of the hemorrhage and aggressive hemodynamic resuscitation. Prophylactic administration of platelets or plasma usually do not prevent coagulopathy [98,99].…”
Section: Transfusion Threshold and Coagulopathy Correctionmentioning
confidence: 99%
“…However, if not corrected, each has a negative influence on survival. Furthermore, subsequent prospective, randomized investigations have demonstrated that rapid rewarming in this patient population does in fact reduce resuscitative volume requirements and perhaps mortality (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated the multifactorial benefits of rapid rewarming of critically injured patients, the most effective of which is extracorporeal blood rewarming (6)(7)(8)(9). The recent limited availability of disposable extracorporeal rewarming circuits caused us to seek an alternative rewarming device.…”
mentioning
confidence: 99%
“…Increase mortality with hypothermia upon admission [53][54][55] Increase mortality at 24 hours with slow rewarming 56 Pregnancy Shifts the oxygen delivery curve to the left Decreases blood flow to the uterus 57,58 May cause fetal bradycardia 58 patients (average intraoperative temperature 34.8°C) took approximately 40 minutes longer to meet discharge criteria from the post anesthesia care unit compared to normothermic patients (average intraoperative temperature 36.7°C) [6]. When a temperature of 36°C was added to discharge criteria, discharge time was prolonged by 90 minutes [6].…”
Section: Traumamentioning
confidence: 99%
“…Hypothermia at admission was also associated with severe functional impairment [53]. Trauma patients admitted to the intensive care unit with hypothermia who were aggressively rewarmed required less intravenous fluids, had a lower oxygen consumption on the second day after trauma, and overall had a lower rate of mortality in the first 24 hours [56]. Thus trauma patients should be rewarmed, especially in the setting of ongoing hemorrhage.…”
Section: Traumamentioning
confidence: 99%